Polynomial Decay Rate for a Coupled Lamé System with Viscoelastic Damping and Distributed Delay Terms. (16th November 2020) - Doudi, Nadjat; Boulaaras, Salah Mahmoud; Alghamdi, Ahmad Mohammed; Cherif, Bahri
Abstract : In this paper, we prove a general energy decay results of a coupled Lamé system with distributed time delay. By assuming a more general of relaxation functions and using some properties of convex functions, we establish the general energy decay results to the system by using an appropriate Lyapunov functional.